PET imaging in patients with brain metastasis—report of the RANO/PET group. Issue 5 (5th January 2019) - Galldiks, Norbert; Langen, Karl-Josef; Albert, Nathalie L; Chamberlain, Marc; Soffietti, Riccardo; Kim, Michelle M; Law, Ian; Le Rhun, Emilie; Chang, Susan; Schwarting, Julian; Combs, Stephanie E; Preusser, Matthias; et al.
Abstract: Brain metastases (BM) from extracranial cancer are associated with significant morbidity and mortality. Effective local treatment options are stereotactic radiotherapy, including radiosurgery or fractionated external beam radiotherapy, and surgical resection. The use of systemic treatment for intracranial disease control also is improving. BM diagnosis, treatment planning, and follow-up is most often based on contrast-enhanced magnetic resonance imaging (MRI). However, anatomic imaging modalities including standard MRI have limitations in accurately characterizing posttherapeutic reactive changes and treatment response. Molecular imaging techniques such as positron emission tomography (PET) characterize specific metabolic and cellular features of metastases, potentially providing clinically relevant information supplementing anatomic MRI. Here, the Response Assessment in Neuro-Oncology working group provides recommendations for the use of PET imaging in the clinical management of patients with BM based on evidence from studies validated by histology and/or clinical outcome.